Surface topography and roughness along the Seti Khola (Pokhara Valley, Nepal) measured in-field in 2016 and 2019 - Fischer, Melanie; Veh, Georg; Korup, Oliver (PANGAEA, 2022)
The Seti Khola (=river) runs along one of the steepest topographic gradients in the Central Himalayas and is the main drainage system of the Pokhara Valley, home to the eponymous city with an estimated population of half a million. In the Pokhara Valley, the Seti Khola runs through a distinct landscape dominated by broad, unpaired, alluvial terraces which abruptly alternate with short (<1 km) reaches, where the river flows through narrow (<10 m) and deep (up to 90 m) gorges. In order to facilitate hydrodynamic modelling of one-dimensional, steady flow in HEC-RAS 5.0.7, we surveyed the Seti Khola's channel and overbank topography as well as surface roughness along a 30-km long reach. During two field-visits (October 2016 and October 2019), we surveyed a total of 95 river cross sections utilising a TruPulse 360 laser range finder and a Garmin eTrex handheld GPS. Additionally, during our October 2019 field-season, we also estimated surface roughness or Manning's n of the Seti Khola's channel and left and right overbank at 61 locations –using the determination methodology described by Arcement Jr and Schneider (1984; doi:10.3133/wsp2339) and Chow (1959).
Keywords: HEC-RAS; hydrodynamic modelling; Manning’s n; outburst flood; river cross sections